Pengaruh Pemberian Coloading Cairan Kristaloid Rl Terhadap Tekanan Darah Sistolik Pada Pasien Intra Anestesi Spinal - Junaidi, Junaidi; Heri Wibowo, Tophan; Sukmaningtyas, Wilis; Budi S, Martyarini (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
Hypotension is a common complication of spinal anesthesia due to sympathetic blockade that triggers vasodilation and decreased vascular tone. This study aims to determine the effect of Ringer's Lactate (RL) crystalloid fluid administration via coloading on the blood pressure of patients undergoing spinal anesthesia. The method used was a quasi-experiment with a pretest-posttest design involving 42 patients at RS Tk. III Dr. Reksodiwiryo Padang. Data were analyzed using the Wilcoxon test due to non-normal data distribution based on the Shapiro-Wilk test. The results showed that before the intervention, 69.0% of respondents experienced systolic hypotension and 19.0% experienced diastolic hypotension. After the coloading intervention, all respondents (100%) no longer experienced hypotension. The Wilcoxon test indicated a significant difference in systolic (Z = - 5.587; p < 0.001) and diastolic (Z = -5.659; p < 0.001) blood pressure before and after coloading. These findings demonstrate that RL crystalloid coloading is effective in preventing intraoperative hypotension.In conclusion, RL coloading has been proven to help maintain hemodynamic stability during spinal anesthesia. This intervention is highly recommended, especially for high-risk patient groups such as women and the elderly. This study also supports the implementation of coloading as a standard protocol in clinical anesthetic practice.